Ensuring Effective Communication in the Diabetes Clinic: Creating a Curve of Remembering - Lathia, Tejal (Journal of Social Health and Diabetes, 2019)
Patient–doctor interview involves exchange of information. Often, consultation may be hurried in resource-constrained settings whereby large quantity of health-related information is delivered to patient in a short period of time. Most people quickly forget what they have heard only once, thus putting into doubt how much of what patients are told, is really comprehended, recalled and thus, acted on. Repeating information, information delivery in staggered format, as well as the use of media for reinforcement helps patients comprehend and recall information better.
Keywords: information; recall; comprehension; closed loop; reinforcement